Audit Committee Diversity toward Voluntary Disclosure Reporting with Existence of Regulatory Regime as Moderation Variable: a Critical Review - Shariff kabara, Ali; Fariha Abdullah, Dewi; Bint Othman, Aniza (International Journal of Engineering and Technology, 2018)
The audit committee is a fundamental and prerequisite tool for fulfilling boardâ€™s monitoring role of ensuring transparency, financial and managerial efficiency. Therefore, it has been applied to address perceived governance failure. This paper aims to critically review the previous literature on the relationship between audit committee diversity as a major corporate governance mechanism and corporate voluntary disclosure reporting (CVDR) with a change in the regulatory regime as moderation variable. This review specifically evaluates theoretical and empirical literature related to audit committee diversity such as independence, financial expertise, accounting expertise; and CVDR in order to highlight some important areas of gaps for future research in this field. It also, emphases the need for a more qualitative method for better understanding of the relationship. This paper proposes that examining the moderating influence of the change of the regulatory regime with regard to CVDR would provide more insight into the link between audit committee diversity and CVDR. The policy implication of the study is also discussed. Lastly, the paper stresses the importance of future studies linking audit committee diversity and CVDR, which are quite scanty the existing literature.Â